2016
DOI: 10.1016/j.jaim.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic, physicochemical and chromatographic characterization of Samasharkara Churna

Abstract: BackgroundSamasharkara Churna, a polyherbal Ayurvedic formulation, is prescribed for treating various conditions such as asthma and cough. Literature review suggested that characterization parameters of Samasharkara Churna are not reported.ObjectiveTo report characteristic parameters of Samasharkara Churna to conform its identity, quality and purity.Materials and MethodsSamasharkara Churna was evaluated for pharmacognostic, physicochemical, microbiological, and chromatographic parameters.ResultsThe chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…After 30 s, the supernatant was collected by centrifugation at 1500 g for 1 min and used for analysis. The quantitative estimation of organo chlorine, organo phosphorous and pyrethroids was carried out using GC/MS analysis in a DB-5 (30 m × 0.25 mm × 0.25 μm) capillary column (Agilent 7000 Triple Quad GC/MS, USA) [17]. Recovery studies with purified compounds indicated that the overall recovery value was 85%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 30 s, the supernatant was collected by centrifugation at 1500 g for 1 min and used for analysis. The quantitative estimation of organo chlorine, organo phosphorous and pyrethroids was carried out using GC/MS analysis in a DB-5 (30 m × 0.25 mm × 0.25 μm) capillary column (Agilent 7000 Triple Quad GC/MS, USA) [17]. Recovery studies with purified compounds indicated that the overall recovery value was 85%.…”
Section: Methodsmentioning
confidence: 99%
“…Further, clean up was carried out as per the procedures given by API [15]. Aflatoxins were estimated using Waters Alliance 2695 HPLC instrument using a Luna C18 column (Phenomenex) of dimensions 4.6 × 150 mm × 5 μ coupled with Waters 2475 fluorescence detector containing Cobra cell [17]. The excitation wavelength and the emission wavelength for fluorescent detection were set at 362 nm and 455 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The solutions thus obtained were observed under visible light and UV light. The characteristic colors appeared were recorded 19,20 .…”
Section: Macroscopic and Microscopic Evaluationsmentioning
confidence: 99%
“…Additionally, the usage of herbal drugs has grown incredibly in line with the worldwide trend of folks returning to natural remedies. The increasing utilization of botanicals by the public is forcing moves to evaluate the health claims of these agents and also to establish specifications of quality and manufacture [1] .Herbal drugs exert a key impact in health care programs particularly in developing nations. However hindrance behind the acceptance of herbal medicine in developed nations is the lack of documentation, stringent quality control measures.…”
mentioning
confidence: 99%